Iddir in Gondar: Historical Development and Its Role in Promoting Social Interaction among Different ‘Ethno-Linguistic’ Groups (1936 -1994) - Fentie, Tesfamichael (Ethiopian Journal of Social Sciences, 2023)
This study explores the genesis and potential roles of iddir in the social interaction of diverse ethno-linguistic groups in Gondar from 1936 to 1994. Although different iddirs have played a dominant role in the integration of different ethnic groups in Gondar since the early Italian invasion of the town, no academic investigation has clearly chronicled their origin and their potential role in promoting social cohesion. The study employed a qualitative method of data collection. The research has extensively used archival, literary and oral sources. Archival sources collected from the Central Gondar Administration Zonal archives all passed through scientific analysis and interpretation controlling for bias, whether the source of data was records, documents, photographs or newspapers. In order to affirm the archival evidence, the researcher also interviewed many elders who were or are members of iddirs, composed of different ethnic groups. The selection of informants was done through the snowball sampling method, and the interview was open-ended. Published materials were also used. The researcher carefully used all the above sources in order to fill the gap in each source of data. The aim of this study was to review the historical development and the roles of iddir in the interaction of different ethno-linguistic groups in Gondar. This study provides original work. Similarly, it avoids the shortage of written documents and fills the gaps. The findings of the study show that indigenous social institutions have roles in enabling the new generation to know what happened in the past, strengthening their mutual understanding and building a sense of belonging. Through iddir, the Gondarines not only participated in funerals but also had opportunities for social interaction, overcoming social problems, the development of friendship, conflict resolution, sharing informationand overcoming economic challenges.